Isolasi Bakteri Indigenus yang Potensial Sebagai Agen Biofertilizer Asal Tanah Gambut di Kawasan Zamrud dan Taman Nasional Tesso Nilo, Riau - Rohyani '; Delita Zul; Bernadeta Leni Fibrianti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Biofertilizer is a substance of functional microorganisms that has a role in providing nutrient for plant and can be used as a substitute for chemical fertilizer. This functional microorganisms such as phosphate solubilizing microorganisms, cellulolytic microorganisms, and nitrogen fixing microorganisms are rich in soil. The purpose of this study was to isolate the indigenous bacteria that are potential as biofertilizer agent. The group fuiontional bacteria was isolated from peat soil in the Zamrud forest and the Tesso Nilo National Park (TNTN) by growing them on suitable selective media. Symbiotic nitrogen fixing bacteria, non symbiotic nitrogen fixing bacteria, phosphate solubilizing bacteria (PSB), and cellulolytic bacteria were isolated using of yeast extract mannitol agar (YEMA) medium, Asby’s mannitol phosphate and NFb media, pikovskaya's medium, and cellulose congo red agar (CCRA) medium, respectively. The potential of isolated bacteria as biofertilizer agent was analyzed qualitatively based on size of clear zone formed around colony of PSB and cellulolytic bacteria, whereas symbiotic nitrogen fixing bacteria were selected by its ability to absorb congo red and non symbiotic nitrogen fixing bacteria were chosen based on its ability to form pellicle and change of medium color. As manys as 170 isolates were succesfully obtained, consisted of 77 isolates of symbiotic nitrogen fixing bacteria, 47 isolates of symbiotic nitrogen fixing bacteria, 74 of PSB, and 19 isolates of cellulolytic bacteria. The potential PSB and cellulolytic bacteria isolated were isolate of FTS1-2AS1 and SZ1-2B2, respectively that showed the highest value of ratio clear zone and diameter colony.